Gluten-free bread with cereal crops flour - Hryshchenko, Anna; Mykhonik, Larysa (My University, 2016)
The results of studies of the effect of different types of gluten-free flour on the production process and quality indicators of gluten-free bread. It is found that the optimum parameters gluten-free bread specific volume achieved in making the formulation of 25% corn flour, rice - 30%, buckwheat - 15%.
Keywords: gluten-free bread; celiac disease; quality of bread; rice flour; corn flour; buckwheat flour; безглютеновий хліб; целіакія; якість хліба; рисове борошно; кукурудзяне борошно; гречане борошно; безглютеновый хлеб; целиакия; качество хлеба; рисовая мука; кукурузная мука; гречневая мука; кафедра технології хлібопекарських і кондитерських виробів